2014
DOI: 10.3389/fnins.2014.00255
|View full text |Cite
|
Sign up to set email alerts
|

Review: evolution of GnIH and related peptides structure and function in the chordates

Abstract: Discovery of gonadotropin-inhibitory hormone (GnIH) in the Japanese quail in 2000 was the first to demonstrate the existence of a hypothalamic neuropeptide inhibiting gonadotropin release. We now know that GnIH regulates reproduction by inhibiting gonadotropin synthesis and release via action on the gonadotropin-releasing hormone (GnRH) system and the gonadotrope in various vertebrates. GnIH peptides identified in birds and mammals have a common LPXRF-amide (X = L or Q) motif at the C-terminus and inhibit pitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 77 publications
0
16
0
Order By: Relevance
“…88 Mammalian GnIH is also known as RFamide-related peptide (RFRP). 89 Two forms of GnIH (RFRP-1 and RFRP-3) have been identified in the human hypothalamus and are able to regulate the HPG axis in men. 90 Hinuma et al 91 identified a specific receptor for mammalian GnIH that was identical to the previously-described receptor, GPR147.…”
Section: The Hpa Axis and Male Fertilitymentioning
confidence: 99%
See 1 more Smart Citation
“…88 Mammalian GnIH is also known as RFamide-related peptide (RFRP). 89 Two forms of GnIH (RFRP-1 and RFRP-3) have been identified in the human hypothalamus and are able to regulate the HPG axis in men. 90 Hinuma et al 91 identified a specific receptor for mammalian GnIH that was identical to the previously-described receptor, GPR147.…”
Section: The Hpa Axis and Male Fertilitymentioning
confidence: 99%
“…92 The molecular details of GnIH are eloquently described elsewhere. 89,90 GnIH neurons are situated in the dorsomedial hypothalamic area in mammals and the PVN in birds. 90 GnIH axon terminals project into the preoptic area where they come in contact with GnRH neurons, and GPR147 has been identified in GnRH neurons, suggesting that direct inhibition occurs.…”
Section: The Hpa Axis and Male Fertilitymentioning
confidence: 99%
“…Syntenic analysis involves the comparison of the locations of orthologous or paralogous genes between chromosomes, within or among species, which facilitates more accurate analyses of the origins and relationships of individual peptide-7TMR families (Cerda-Reverter et al ., 2000; Lagerstrom et al ., 2005; Lee et al ., 2009; Kim et al ., 2011, 2012; Dores, 2013; Osugi et al ., 2014). However, small scale synteny analysis is only suitable for determining the evolutionary history of closely related families.…”
Section: Phylogeny and Synteny For Delineating Gene Family Emergencementioning
confidence: 99%
“…They also underline some neuropeptide families (e.g., CCK/sulfakinins) in which the RFamide motif is unique to protostomian members. Osugi et al ( 12 ) show that identification of GnIH in agnathans (lamprey) and amphioxus reveals that the C-terminal amide motif of GnIH can differ, being QPQRF or RPQRF, in addition to previously observed LPXRF in birds, mammals and most of fish, and MPQRF in grass puffer and medaka.…”
mentioning
confidence: 94%
“…The review by Ayachi and Simonin ( 21 ) presents the emerging evidences in rodents that all RF-amide peptides and their receptors are involved in the modulation of nociception in basal and chronic pain conditions, as well as of opioid-induced hyperalgesia. The reviews on GnIH by Osugi et al ( 12 ) and by Ogawa and Parhar ( 22 ) report that even if the inhibitory role of GnIH is well established in later-evolved vertebrates, such as birds and mammals, the situation is less clear in teleosts and may vary according to the maturational stage. Comparative studies have the potential to reveal novel regulatory mechanisms that could give a better comprehension of physiological functions.…”
mentioning
confidence: 99%